The Turkish adaptation of the athletic perceptions of Performance Scale: shame, guilt, and performance concerns and their associations with mental health problems among Turkish elite-level adult athletes - Lima, Y.; Yilmaz, N. D.; Denerel, N.; Dogan, E.; Treeby, M. S.; Rice, S. (The Journal of Sports Medicine and Physical Fitness, 2025)
BACKGROUND: There are many sport-specific factors in daily sport/competition environment that may negatively affect athletes and cause athletic shame or guilt linked with mental health problems. The aim of the present study was to establish psychometric data for the Turkish version of the Athletic Perceptions of Performance Scale (APPS-Tr) and evaluate correlates of athletic shame and guilt among adult Turkish professional athletes.